FMRI‐Based Brain Responses to Olfactory Stimulation with Two Putatively Orexigenic Functional Food Ingredients at Two Different Concentrations in the Pig Model. Issue 9 (23rd August 2019) - Coquery, Nicolas; Menneson, Sophie; Meurice, Paul; Janvier, Régis; Etienne, Pierre; Noirot, Virginie; Val‐Laillet, David
Abstract : Abstract: Natural plant extracts are increasingly used as functional feed ingredients in animal husbandry and food ingredients in human alternative medicine to improve welfare and health. We investigated in 20 growing pigs via functional magnetic resonance imaging (fMRI) the brain blood oxygen level–dependent (BOLD) responses to olfactory stimulation with two sensory functional feed ingredients, A and B, at two different concentrations. Functional ingredient A contained extracts from Citrus sinensis (60% to 80%), and ingredient B contained a mixture of extracts Oreganum vulgarae (40% to 55%) and Cymbopogon flexuosus (20% to 25%). Increased concentration of ingredients induced a higher activation in reward and cognitive areas compared to lower concentrations. Moreover, considering both ingredients at the highest concentration, the ingredient A elicited higher brain responses in brain areas involved in hedonism/pleasantness compared to ingredient B, and more specifically in the caudate nucleus and orbitofrontal cortex. Our findings shed new light in the scope of emotion regulation through olfactory modulation via sensory functional ingredients, which opens the way to further preclinical studies in animal models and translational research in the context of nutrition, welfare, and health. Practical Application: Functional food/feed ingredients are gaining interest for improving health and welfare in humans and animals. Besides representing an alternative to antibiotics for example, food ingredients and their sensory characteristics might have a positive impact on emotions and consequently on well‐being. Functional brain imaging in large animals such as in the pig model is a promising approach to investigate the central and behavioural effects of food ingredients, and determine the most effective blends and concentrations to modulate internal and emotional states.